Resolving Socio-Religious Land Conflict: Heritage Preservation and Da'wah on Kemaro Island, Palembang - Herison, Herison; Romli, Romli; Barkah, Qodariah; Mikail, Kiki (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
This study aims to investigate the underlying factors, resolution strategies, and impediments concerning the land dispute on Kemaro Island between the Palembang City Government and the descendants of Kiai Merogan. Methodologically, this research employed a qualitative approach, utilising data collection techniques such as observation, document analysis, and interviews with key informants including descendants, government officials, and island managers, selected for their direct knowledge and involvement. Findings reveal that the conflict, stemming from government tourism development plans clashing with the descendants' historical land claims, initially escalated when development proceeded amidst ongoing litigation. However, subsequent dialogue successfully de-escalated tensions, leading to a shared vision for development. Key agreements included joint management oversight, the relinquishing of exclusive ownership claims by both parties, and a commitment to expedite the development process. The Mayor's withdrawal of legal proceedings and the family's advocacy for religious tourism were significant factors. Crucially, the proposal for an Islamic Centre, integrating religious, educational, and community functions, proved instrumental in reconciling the parties' interests. The study concludes that effective land dispute resolution in such contexts necessitates approaches that account for complex socio-cultural and religious dynamics, prioritising collective welfare and dialogue over purely legalistic frameworks.